Forest Urbanisms (Leuven University Press, 2024)
How forest urbanism can address the contemporary socio-ecological crisis. A radical redefinition of how humanity occupies the earth — through forests, agriculture, and settlement — and rearticulates environmental stewardship by intertwining ecologies and urbanisms, this publication brings together essays by scholars in forestry, urbanism and other disciplines, designers, practitioners and policy makers. It explores the multifaceted notion of forest urbanisms, including a conceptual framing essay; contributions from the sciences such as bioscience engineering, architecture, urbanism and public policy; contemporary forest urbanism projects and explorative essays that make tangible an agenda for the 21st century. With descriptions of both built and non-built projects from around the globe, the essays show how such projects substantiate a radical shift in humankind’s occupation of the world, where ecologies and urbanisms converge and agriculture, forests, and settlements are integrated. Forest Urbanisms extends growing research on a new nature–culture relationship, the necessity for trees in cities, and a rebalancing of ecology and urbanism.